2012
DOI: 10.1186/1550-2783-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Dose response effects of a caffeine-containing energy drink on muscle performance: a repeated measures design

Abstract: BackgroundEnergy drinks have become the most used caffeine-containing beverages in the sport setting. The aim of this study was to determine the effects of two doses of a caffeine-containing energy drink on muscle performance during upper- and lower-body power-load tests.MethodsIn a randomized order, twelve active participants ingested 1 and 3 mg of caffeine per kg of body weight using a commercially available energy drink (Fure®, ProEnergetics) or the same drink without caffeine (placebo; 0 mg/kg). After sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 47 publications
6
91
2
3
Order By: Relevance
“…Nevertheless, our data have shown that a dose of 3 mg·kg −1 of caffeine improved both peak and mean power during the test. Likewise, recent research has demonstrated an ergogenic effect in power activities, both in lower and upper limb exercises, such as power in half squats or bench presses, jumps, or repeated jumps in 15 s [2,5,8]. This ergogenic effect in anaerobic performance could be due to the influence of caffeine on the Na+/K+ pump, facilitating Na+/K+ATPase activity [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, our data have shown that a dose of 3 mg·kg −1 of caffeine improved both peak and mean power during the test. Likewise, recent research has demonstrated an ergogenic effect in power activities, both in lower and upper limb exercises, such as power in half squats or bench presses, jumps, or repeated jumps in 15 s [2,5,8]. This ergogenic effect in anaerobic performance could be due to the influence of caffeine on the Na+/K+ pump, facilitating Na+/K+ATPase activity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were encouraged to go to bed at their habitual bedtime and to report any sleeping issues during the night. The morning following the experimental trial, participants were required to fill out a questionnaire that has been previously used to assess the perceptible side effects of caffeinated energy drinks in the sports context [17] and laboratory conditions [8]. This questionnaire included information about sleep quality, prevalence of gastrointestinal problems, muscular pain and headache, and self-perception of nervousness or increased activeness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that there were no significant differences between trials in any anaerobic power measure. In a recent publication, 12 healthy male and female non-resistance trained participants ingested a commercially available ED standardized at either 1 or 3 mg·kgBM -1 of caffeine or a placebo beverage (containing no caffeine) in a randomized, repeated measures design [65]. Sixty minutes following beverage ingestion, each participant completed 10-to-100% 1RM power-load tests for the bench press and half-squat.…”
Section: Exercise Performancementioning
confidence: 99%
“…Ingestion of the ED with 1 mg·kgBM -1 of caffeine was not enough to raise the power output during the power-load tests. However, the ingestion of an ED with 3 mg·kgBM -1 of caffeine increased maximal power output by 7% in both the half-squat and bench-press as compared to the ingestion of a placebo [65]. A recent study by Gonzalez and colleagues [174] indicated that an energy matrix consisting of caffeine, taurine and glucoronolactone consumed 10-min prior to a workout resulted in an 11.9% improvement (p < 0.05) in the number of repetitions performed during 4 sets of the squat or bench press exercise using 80% of the subject’s 1-RM.…”
Section: Exercise Performancementioning
confidence: 99%